2023
DOI: 10.1021/acssuschemeng.2c07375
|View full text |Cite
|
Sign up to set email alerts
|

Transition into Net-Zero Carbon Community from Fossil Fuels: Life Cycle Assessment of Light-Driven CO2 Conversion to Methanol Using Graphitic Carbon Nitride

Abstract: Direct conversion of waste CO2 into CH3OH by solar irradiation has emerged as the most enthralling alternative to conventional steam methane reforming, which reduced the concentration of greenhouse gases and the consumption of fossil resources. A cradle-to-gate life cycle assessment was carried out to assess the environmental feasibility of implementing the current g-C3N4-based photocatalytic CO2 reduction system based on 1 kg CH3OH production. It was observed that the emerging photocatalytic CH3OH system indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Additionally, carbon footprint unveils that the electrochemical process will be competitive among all three processes when coupled with electricity with a CI of 0.25 kg CO 2 eq/kWh or lower and is estimated to achieve carbon neutrality when powered by electricity with a CI of 0.12 kg CO 2 eq/kWh. As such, to achieve future commercialization of electrochemical ethanol production technology, more research efforts are urgently required to develop low-carbon electricity sources, particularly those derived from renewable energy, to eliminate the intrinsic great carbon footprint attributed to the conventional electricity mix …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, carbon footprint unveils that the electrochemical process will be competitive among all three processes when coupled with electricity with a CI of 0.25 kg CO 2 eq/kWh or lower and is estimated to achieve carbon neutrality when powered by electricity with a CI of 0.12 kg CO 2 eq/kWh. As such, to achieve future commercialization of electrochemical ethanol production technology, more research efforts are urgently required to develop low-carbon electricity sources, particularly those derived from renewable energy, to eliminate the intrinsic great carbon footprint attributed to the conventional electricity mix …”
Section: Discussionmentioning
confidence: 99%
“…The summarized research demonstrated that multiple value-added chemicals or fuels can be produced from CO 2 hydrothermal conversion, as depicted in Figure 17a REVIEW Figure 17 (a) Main products that can be obtained by hydrothermal CO 2 conversion 33-35, 39, 40, 48, 50, 79, 81, 87, 88, 90, 91, 96, 98, 105, 109-112 , (b) Comparison of formic acid production efficiency by different CO 2 catalytic methods 48,51,79,88,90,96,107,[113][114][115][116][117][118][119][120][121][122][123][124][125][126] , (c) comparison of greenhouse gas emissions by different CO 2 catalytic methods 89,[127][128][129][130][131][132][133][134][135][136] (yellow balls represent photocatalysis, brown balls represent electrocatalysis, blue balls represent catalytic hydrogenation, green balls represent biomass and regenerable metals).…”
Section: The Assessment Of Carbon Emission Budget and Efficiency Of C...mentioning
confidence: 99%
“…For instance, Ling et al achieved a reduction in greenhouse gas concentration and fossil resource consumption through the direct conversion of waste CO 2 into methanol by solar irradiation, with a LCA indicating that the emerging photocatalytic system induces 68% less carbon Figure 10. Comprehensive life cycle assessment of photocatalytic CO2 reduction system compared to conventional steam methane reforming [196]. Reprinted with permission from [196].…”
Section: Environmental Aspects and Sustainability Impact Towards Circ...mentioning
confidence: 99%